Recent advances in non-specific immune memory against bovine tuberculosis - Blanco, Federico Carlos (2021)
Bovine tuberculosis is an important worldwide disease mainly related to cattle, although it also affects other mammals, including humans. In recent years, there have been considerable advances in the knowledge of the immune response mechanisms underlying the interaction of Mycobacterium bovis, the main agent of bovine tuberculosis, with its hosts. In this review we describe the most recent findings on the cattle immune response to M. bovis, particularly regarding trained innate immune responses and γδ T cells, that could support the development of vaccines and diagnostic tools to control this disease.